Gestión de proyectos a la creación de un portal web para una unidad educativa - Panchana, J. (2009)
A project is a planification that consists in a group of activities that are found interrelated and coordinated, they have a beginning and an end, being successful or a failure. The direction or project management is the application of the knowledge, abilities, tools and techniques in the activities of a project to satisfied the requirement of it. The objective of this document is to inform about the phases involve in the creation of a web portal for educational unity, following the lineament of a PMBOK Guide (is an stander in the management of the development of projects from the Administration of Project Institute - PMI). The web portal came about as the result of the problem that the professors of the institute had, while inputing the scholar grades and homework scores, so the parents will be familiarized with the activities of their representatives in the institution and to present to the public a more dynamic image of the institution, their ideals and objectives in the teaching of the Ecuadorian children and young adults.